2010
DOI: 10.1161/circulationaha.110.961193
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Suppresses the Type I Interferon Response, a Family of Potent Antiviral Immunoregulators, in Macrophages Challenged With Lipopolysaccharide

Abstract: Background-High-density lipoprotein (HDL) protects the artery wall by removing cholesterol from lipid-laden macrophages.However, recent evidence suggests that HDL might also inhibit atherogenesis by combating inflammation. Methods and Results-To identify potential antiinflammatory mechanisms, we challenged macrophages with lipopolysaccharide, an inflammatory microbial ligand for Toll-like receptor 4. HDL inhibited the expression of 30% (277 of 911) of the genes normally induced by lipopolysaccharide, microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 47 publications
4
104
0
1
Order By: Relevance
“…rHDL significantly reduced endotoxemia-induced inflammatory response, as it reduced clinical symptoms, reduced inflammatory cytokine (TNF-α, IL-6, IL-8) production, and attenuated LPS-induced leukocyte activation, in part due to the downregulation of the main LPS receptor monocyte-bound CD14 (Pajkrt et al 1996). In LPS-challenged macrophages, HDLs selectively inhibit the activation of type I IFN response genes (Suzuki et al 2010), which play a critical role in the antiviral response of cells, although emerging evidence also implicates this response in host defense during bacterial infection. This inhibitory effect of HDL does not require LPS binding to lipoproteins (Suzuki et al 2010).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…rHDL significantly reduced endotoxemia-induced inflammatory response, as it reduced clinical symptoms, reduced inflammatory cytokine (TNF-α, IL-6, IL-8) production, and attenuated LPS-induced leukocyte activation, in part due to the downregulation of the main LPS receptor monocyte-bound CD14 (Pajkrt et al 1996). In LPS-challenged macrophages, HDLs selectively inhibit the activation of type I IFN response genes (Suzuki et al 2010), which play a critical role in the antiviral response of cells, although emerging evidence also implicates this response in host defense during bacterial infection. This inhibitory effect of HDL does not require LPS binding to lipoproteins (Suzuki et al 2010).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 95%
“…In LPS-challenged macrophages, HDLs selectively inhibit the activation of type I IFN response genes (Suzuki et al 2010), which play a critical role in the antiviral response of cells, although emerging evidence also implicates this response in host defense during bacterial infection. This inhibitory effect of HDL does not require LPS binding to lipoproteins (Suzuki et al 2010). HDLs (and apoA-I) attenuate also LPS-induced neutrophil activation (Murphy et al 2011).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 99%
“…During the acute phase response, levels of serum amyloid A increase dramatically and are found in the plasma associated with HDL-sized lipoproteins, whereas ApoA-I may dissociate from HDL and be catabolized, reducing plasma levels of ApoA-I HDL ( 46 ). Suzuki et al (47) have recently shown that HDL is protective in mice infected with Salmonella typhimurium , preventing increases in plasma levels of interferon-␤ . The greater HDL affi nity of one ApoA-I protein over another may play a role in the response to an infl ammatory challenge.…”
Section: /Apoementioning
confidence: 99%
“…In recent cell culture studies with animal and human cells, HDL promoted cholesterol effl ux from macrophage foam cells in atheromatous vessels, reducing the cholesterol burden and macrophage-driven infl ammation ( 33,35 ). HDL also inhibits the type I interferon response pathway independently of macrophage cholesterol stores ( 36 ) and activates the complement cascade ( 37,38 ). Furthermore, HDL-C not only inhibits LDL-induced lipid hydroperoxide Supplemental Material can be found at:…”
Section: Strengths and Limitations Of The Current Studymentioning
confidence: 99%